Experimental observations on the response of 1 and 2 order fibre optic long period grating coupling bands to the deposition of nanostructured coatings - James, Stephen W.; Cheung, C. S.; Tatam, Ralph P. (Cranfield University, 2007)
The sensitivity of attenuation bands corresponding to the 2nd order coupling to cladding modes by a fibre optic long period grating (LPG) to the deposition of nanostructured coatings is investigated and compared with that of the 1st order coupling. The experimental observations support previously reported theoretical descriptions of LPGs with nanoscale coatings.
Keywords: Fiber optics sensors, Gratings, Deposition and fabrication